(untitled) (Eurasian Journal of Engineering and Technology, 2024)
The aim of this study is to present a novel exploration for obtaining an enhanced version of the MFCC algorithm to capitalize on its superior quality in sound analysis and voiceprint extraction. The objective is to overcome challenges in using the MFCC algorithm in real-world and highly noisy environments, where speech is susceptible to noise and interference in natural settings. This, in turn, diminishes the performance of the MFCC-based system in real-world applications